DeLone and McLean Model Testing upon The Information System Implementation of New Student Enrolment at Junior High school Level in Pekalongan City - Christian Yulianto Rusli; Faizal Kurniawan; Prastuti Sulistyorini (Politeknik Negeri Semarang, 2023)
The information technology based Information System in education has been used in responding the change and as a tool in maintaining efficiency and effectiveness, especially for the online system ofÂ new student admission (PPDB).Â The Pekalongan City Education, since 2014, has developed an online junior high school New Student Admission application. This system was built to handle the process of admitting new students, from registration, selection to announcement of selection result. Even though it has been implemented for 6 years, the measurement of the success of implementing PPDB online has not been carried out. The purpose of researching is to determine the success of implementing the PPDB online information system for junior high school level. The modified DeLone and McLean model was used to measure the success of online PPDB. Research respondents were all admin and operators of the online PPDB system as many as 92 respondents. The data analysis method for processing variables used linear regression statistical analysis. The test results show that system quality, information quality, service quality, and user satisfaction have a significant and significant effect on net benefits, so that users benefit from the online PPDB information system.